STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENUMBUHKAN ANTUSIAS BELAJAR MELALUI KUIS INTERAKTIF PADA SISWA SDN 2 BATARAGURU - Khunute Mar Talley; Darmayanti; Muhamad Ridwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the strategies employed by Islamic Religious Education teachers in fostering students’ learning enthusiasm through the implementation of interactive quizzes and to analyze students’ responses to the use of these quizzes at SDN 2 Bataraguru. The research method used was a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. The interviews were conducted in a semi-structured manner to explore information regarding learning strategies, the use of interactive quizzes, and students’ responses during the learning process. The results indicate that teachers applied various learning strategies, such as ice-breaking activities, discussions, question-and-answer sessions, the use of Student Worksheets (LKPD), and the utilization of digital media such as Wordwall and Canva. The implementation of interactive quizzes was able to create a more dynamic learning atmosphere, increase student participation, and reduce boredom in learning. Students showed active and enthusiastic responses and became more confident in answering questions. Supporting factors in the implementation of interactive quizzes include the availability of facilities such as LCD projectors and adequate internet access. Meanwhile, inhibiting factors include network disturbances and unfavorable weather conditions. This study concludes that interactive quizzes are an effective strategy for fostering students’ learning enthusiasm in Islamic Religious Education. Therefore, teachers are encouraged to continue developing innovative learning strategies that are in line with students’ needs.